PENGARUH CORPORATE SOCIAL RESPONSIBILITY DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN - Umro, Madinatul; Fidiana, Fidiana (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2016)
The firm value in this research is reflected by the stock price of a company. The firm value enhancement to attraction for investors to undertake investment activities of the company. This research is meant to test the influence of Corporate Social Responsibility (CSR) and the profitability to the firm value. The samples are 10 companies which are engaged in the field chemical sector which are listed in Indonesia Stock Exchange (IDX) in 2010-2014 periods. The sample collection technique has been done by using purposive sampling technique. Based on the sample collection technique, 6 companies which are fulfilled the criteria have been selected as samples. The total amount of 6 companies and 5 years of observation period are 30 observations and in order to test these observations have been done by using multiple linear regressions. Based on the result of multiple linear tests, first, hypothesis states that the Corporate Social Responsibility (CSR) has positive influence to the firm value and second, profitability does not have any influence to the firm value.Keywords: Corporate Social Responsibility (CSR), Profitability, Firm Value.